2011
DOI: 10.1007/s00382-011-1235-6
|View full text |Cite
|
Sign up to set email alerts
|

The Intra-Seasonal Oscillation and its control of tropical cyclones simulated by high-resolution global atmospheric models

Abstract: Project Athena is an international collaboration testing the efficacy of high-resolution global climate models. We compare results from 7-km mesh experiments of the Nonhydrostatic Icosahedral Atmospheric Model (NICAM) and 10-km mesh experiments of the Integrated Forecast System (IFS), focusing on the Intra-Seasonal Oscillation (ISO) and its relationship with tropical cyclones (TC) among the boreal summer period (21 May-31 Aug) of 8 years (2001)(2002)(2004)(2005)(2006)(2007)(2008)(2009)). In the first month of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 86 publications
4
55
1
Order By: Relevance
“…Although the representation of vertical velocity depends on the horizontal resolution (Miyamoto et al 2013(Miyamoto et al , 2015, relatively coarser resolution simulations with a horizontal grid interval of approximately 7 or 14 km reproduce structures of TCs and deep convective cloud systems using NICAM (Miura et al 2007;Yamada et al 2010;Satoh et al 2012a;Yamada and Satoh 2013;Miyakawa et al 2014;Nakano et al 2015). In this study, the simulation data for an integration period of 20 years with a horizontal grid interval of about 14 km is used to obtain sufficient samples of TCs.…”
Section: Model and Experimentsmentioning
confidence: 99%
“…Although the representation of vertical velocity depends on the horizontal resolution (Miyamoto et al 2013(Miyamoto et al , 2015, relatively coarser resolution simulations with a horizontal grid interval of approximately 7 or 14 km reproduce structures of TCs and deep convective cloud systems using NICAM (Miura et al 2007;Yamada et al 2010;Satoh et al 2012a;Yamada and Satoh 2013;Miyakawa et al 2014;Nakano et al 2015). In this study, the simulation data for an integration period of 20 years with a horizontal grid interval of about 14 km is used to obtain sufficient samples of TCs.…”
Section: Model and Experimentsmentioning
confidence: 99%
“…The domain covering Bebinca and the northern convection region was less than 1500 km from the stretched center, and the grid interval within this domain was less than 7 km. Although it may appear that this resolution is not sufficiently fine for simulating mesoscale convection, NICAM has been shown to realistically reproduce cloud system behavior of tropical convection, including the Madden-Julian oscillation and TCs with grid intervals of 7 km (Miura et al 2007;Fudeyasu et al 2008;Oouchi et al 2009;Satoh et al 2012).…”
Section: Model Descriptionmentioning
confidence: 99%
“…More statistical results for MJO simulations are shown by Miyakawa et al (2014), who reported a good performance of MJO predictability by the hind cast approach with NICAM. BSISO simulations were analyzed by Oouchi et al (2009aOouchi et al ( , 2014, Taniguchi et al (2010), Yanase et al (2010b), and Satoh et al (2012a). In particular, they focused on relations between ISV and tropical cyclones, as described below, since ISV modulates large-scale vorticity distributions that generally lead to preferable conditions for cyclogenesis.…”
Section: Scientific Overview Of Nicammentioning
confidence: 99%
“…For example, Satoh et al (2012a) analyzed 8 years of boreal summer experiments that were conducted in the Athena Project (Kinter et al 2013) in order to show the simulated climatology of tropical cyclones and produced results that show good relations between tropical cyclone activities and MJO activities. Future changes in the tropical cyclone structure were analyzed by Yamada et al (2010Yamada et al ( , 2012, Yamada and Satoh (2013), and Emanuel et al (2010).…”
Section: Scientific Overview Of Nicammentioning
confidence: 99%